Dietary behaviour change intervention for managing sarcopenic obesity among community-dwelling older people: a pilot randomised controlled trial - Yin Yue-Heng; Liu Justina Yat Wa; Välimäki Maritta (BMC, 2025)
Background The effects of dietary intervention in managing sarcopenic obesity are controversial, and behavior change techniques are lacking in previous studies which are important for the success of dietary intervention. This study aimed to evaluate the feasibility and preliminary effects of a dietary behaviour change (DBC) intervention on managing sarcopenic obesity among community-dwelling older people in the community.
Methods A two-armed, RCT was conducted. Sixty community-dwelling older adults (>= 60 years old) with sarcopenic obesity were randomised into either the experimental group (n = 30), receiving a 15-week dietary intervention combined with behaviour change techniques guided by the Health Action Process Approach model, or the control group (n = 30), receiving regular health talks. Individual semi-structured interviews were conducted with 21 experimental group participants to determine the barriers and facilitators of dietary behaviour changes after the intervention.
Results The feasibility of the DBC intervention was confirmed by an acceptable recruitment rate (57.14%) and a good retention rate (83.33%). Compared with the control group, the experimental group significantly reduced their body weight (p = 0.027, d = 1.22) and improved their dietary quality (p < 0.001, d = 1.31). A positive improvement in handgrip strength (from 15.37 +/- 1.08 kg to 18.21 +/- 1.68 kg), waist circumference (from 99.28 +/- 1.32 cm to 98.42 +/- 1.39 cm), and gait speed (from 0.91 +/- 0.02 m/s to 0.99 +/- 0.03 m/s) was observed only in the experimental group. However, the skeletal muscle mass index in the experimental group decreased. The interview indicated that behaviour change techniques enhanced the partcipants' compliance with their dietary regimen, while cultural contextual factors (e.g., family dining style) led to some barriers.
Conclusion The DBC intervention could reduce body weight, and has positive trends in managing handgrip strength, gait speed, and waist circumference. Interestingly, the subtle difference between the two groups in the change of muscle mass index warrants futures investigation. This study demonstrated the potential for employing dietary behaviour change interventions in community healthcare.